PEM electrolytic cell porous transmission layer and preparation method thereof

By loading precious metals on the titanium-based sheet of the porous transport layer of the PEM electrolytic cell and calcining the contact resistance problem caused by the oxidation of the porous transport layer is solved, and the activity and performance of the electrolytic cell are improved.

CN119571350APending Publication Date: 2025-03-07BEIJING CEI TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411494256.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The porous transport layer of the existing PEM electrolytic cell is easily oxidized, which increases the contact resistance with the membrane electrode and affects its electrochemical performance.

Method used

A preparation method is adopted, including substrate preparation, electrolyte preparation, electrodeposition and calcination treatment steps. The specific steps are: cutting and pretreating the titanium-based sheet, preparing a precious metal solution and electrodeposition, and finally calcining to obtain a porous transport layer of the PEM electrolytic cell.

Benefits of technology

By loading precious metals, the porosity of the porous transport layer is improved, the contact resistance between the porous transport layer and the membrane electrode is reduced, and the activity and performance of the electrolytic cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571350A_ABST
    Figure CN119571350A_ABST
Patent Text Reader

Abstract

The invention discloses a PEM electrolytic cell porous transmission layer and a preparation method thereof. The preparation method comprises the steps that a titanium-based sheet material is cut according to a preset size, a substrate is obtained after pretreatment, and the titanium-based sheet material is a titanium felt or porous titanium; precious metal is dissolved in pure water to obtain a metal solution, a stabilizer is added into the metal solution, and electrolyte is obtained after stirring; a substrate serving as a working electrode, a platinum sheet serving as a counter electrode and a saturated calomel electrode serving as a reference electrode are placed in the electrolyte, precious metal is deposited on the substrate under preset electrodeposition parameters, and a sample is obtained after cleaning and airing; the sample is placed in a tubular furnace to be calcined, and the PEM electrolytic cell porous transmission layer is obtained through aftertreatment. According to the technical scheme, the porous transmission layer of the PEM electrolytic cell prepared through the technical steps can improve the porosity of the porous transmission layer, reduce the contact resistance between the porous transmission layer and a membrane electrode and improve the activity of the electrolytic cell, so that the purpose of improving the performance of the electrolytic cell is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of hydrogen production, and in particular to a porous transmission layer of a PEM electrolyzer and a preparation method thereof. Background Art

[0002] PEMWE (Proton Exchange Membrane Water Electrolysis) hydrogen production has the advantages of high efficiency, fast dynamic response, and high H2 purity. PEMWE technology has gradually been commercialized in recent years. However, due to the component-specific and highly coupled thermal, electronic and mass transfer mechanisms, mass transfer losses continue to plague PEM electrolyzer technology. The latest research shows that for a typical PEM electrolyzer, mass transport mainly occurs at the porous transport layer / catalyst layer (Porous Transport Layer, PTL / Catalyst Layer, CL) interface. Therefore, the PTL in the electrolyzer is an important PEMWE cell component.

[0003] At present, almost all PEM electrolyzers use titanium-based materials for PTL. The titanium-based porous transport layer (PTL) is affected by surface passivation (titanium oxidation), which increases the contact resistance between the PTL and the membrane electrode, and ultimately operates at a higher cell voltage and cannot perform well, becoming one of the important factors limiting the widespread application of PEMWE. Summary of the invention

[0004] The present application provides a porous transport layer of a PEM electrolyzer and a preparation method thereof, aiming to solve the problem in the prior art that the porous transport layer is easily oxidized to increase the contact resistance between the porous transport layer and the membrane electrode, thereby affecting its electrochemical performance.

[0005] To achieve the above objectives, the present application proposes a method for preparing a porous transport layer of a PEM electrolyzer, the method comprising:

[0006] Substrate preparation step: cutting the titanium-based sheet material into a preset size and obtaining the substrate after pretreatment; the titanium-based sheet material is titanium felt or porous titanium;

[0007] The electrolyte preparation step is: dissolving the precious metal in pure water to obtain a metal solution, adding a stabilizer to the metal solution, and stirring to obtain an electrolyte;

[0008] Electrodeposition step: using the substrate as a working electrode, a platinum sheet as a counter electrode, and a saturated calomel electrode as a reference electrode in the electrolyte, depositing the noble metal on the substrate under preset electrodeposition parameters, and obtaining a sample after washing and drying;

[0009] Calcination treatment step: placing the sample in a tubular furnace for calcination, and then post-processing to obtain a porous transport layer of a PEM electrolyzer.

[0010] In some embodiments, in the substrate preparation step, the cutting size of the titanium-based sheet is not less than 5*5 cm.

[0011] In some embodiments, the pretreatment includes immersing the titanium-based sheet in an ultrasonic bath in a mixed cleaning solvent of 2-propanol and acetone for 15 to 20 minutes, and then rinsing with deionized water.

[0012] In some embodiments, in the electrolyte preparation step, the precious metal includes at least two of RuCl3, IrCl3, CeCl3 and PtCl2;

[0013] Among them, the concentration ranges of RuCl3, IrCl3, CeCl3 and PtCl2 after dissolving in pure water are respectively 30-40g / L, 40-60g / L, 35-75g / L and 30-80g / L.

[0014] In some embodiments, the stabilizer is a mixed solution of PUB, BPC and sodium citrate, in which the concentrations of PUB, BPC and sodium citrate are in the range of 6-8 mL / L, 1-3 mL / L and 60-80 g / L, respectively.

[0015] In some embodiments, the stirring time is 15 to 20 minutes, and the stirring temperature is 25 to 30°C.

[0016] In some embodiments, in the electro-deposition step, the electro-deposition parameters include: the electrolyte temperature is 25-30° C., nitrogen is introduced throughout the electro-deposition process, and the precious metal is deposited on the substrate at a voltage of 1.2-1.4V for 4-10 minutes.

[0017] In some embodiments, during the calcination step, nitrogen is introduced into the tubular furnace to calcine the sample at a temperature of 250 to 550° C. for 1 to 3 hours.

[0018] In some embodiments, the post-treatment includes adding the calcined sample into pure water and then washing it in an ultrasonic machine for 10 to 15 minutes.

[0019] The present application also provides a porous transport layer for a PEM electrolyzer, which is prepared using the method for preparing the porous transport layer for a PEM electrolyzer as described above.

[0020] The technical solution of the present application proposes a porous transport layer of a PEM electrolyzer and a preparation method thereof, and the preparation method includes a substrate preparation step, an electrolyte preparation step, an electrodeposition step, and a calcination treatment step. Specifically, it includes: cutting the titanium-based sheet according to a preset size, obtaining the substrate after pretreatment, and the titanium-based sheet is titanium felt or porous titanium; dissolving the precious metal in pure water to obtain a metal solution, and adding a stabilizer to the metal solution, and obtaining an electrolyte after stirring; using the substrate as a working electrode, a platinum sheet as a counter electrode, and a saturated calomel electrode as a reference electrode in the electrolyte, depositing the precious metal on the substrate under preset electrodeposition parameters, and obtaining a sample after washing and drying; placing the sample in a tubular furnace for calcination, and then obtaining the porous transport layer of the PEM electrolyzer after post-treatment. The porous transport layer of the PEM electrolyzer prepared by the above technical steps in the technical solution of the present application is to load precious metals on titanium felt or porous titanium, thereby increasing the porosity of the porous transport layer, reducing the contact resistance between the porous transport layer and the membrane electrode, and improving the activity of the electrolyzer, thereby achieving the purpose of improving the performance of the electrolyzer. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work, among which:

[0022] Figure 1 This is a schematic diagram of a process for preparing a porous transport layer of a PEM electrolyzer according to an embodiment of the present application;

[0023] Figure 2 This is a performance diagram of polarization curve test of the porous transport layer of the PEM electrolyzer prepared in Examples 1-4 and the comparative example in this application. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0025] See also Figure 1 As shown, the present application proposes a method for preparing a porous transport layer of a PEM electrolyzer, the method comprising:

[0026] Substrate preparation step 10: Cut the titanium-based sheet into a preset size and obtain the substrate after pretreatment; the titanium-based sheet is titanium felt or porous titanium.

[0027] Among them, titanium felt or porous titanium has good conductivity and corrosion resistance, and is a common material choice for the porous transport layer of the PEM electrolyzer. When selecting the cutting size, the cutting size is not less than 5*5cm, so as to ensure that the substrate has sufficient area to support the subsequent electrodeposition and calcination treatment steps, and meet the performance requirements of the porous transport layer of the PEM electrolyzer.

[0028] After the cutting is completed, the cut titanium-based sheet needs to be pretreated to obtain the substrate. The pretreatment includes soaking the titanium-based sheet in an ultrasonic bath in a mixed cleaning solvent of 2-propanol and acetone for 15 to 20 minutes, and then rinsing with deionized water. Among them, 2-propanol and acetone both have good solubility and volatility, and can quickly remove pollutants such as oil and dust on the surface of the titanium-based sheet. Fully soaking for 15 to 20 minutes ensures that the solvent is fully effective, and at the same time, it can avoid the damage to the sheet that may be caused by excessive soaking; and during the soaking process, an ultrasonic bath is used for cleaning. The high-frequency vibration of the ultrasonic wave can generate strong microjets and shock waves, which effectively remove tiny particles and pollutants on the surface of the titanium-based sheet. Finally, after the ultrasonic cleaning is completed, the titanium-based sheet is rinsed with deionized water to remove residual solvents and impurities, while avoiding the introduction of new pollutants.

[0029] Electrolyte preparation step 20: dissolving the precious metal in pure water to obtain a metal solution, adding a stabilizer to the metal solution, and stirring to obtain an electrolyte.

[0030] Among them, adding an appropriate amount of stabilizer to the metal solution can improve the stability of the electrolyte and the deposition efficiency of the noble metal, and stirring can promote the dissolution and dispersion of the stabilizer. Preferably, the stirring time is 15 to 20 minutes and the stirring temperature is 25 to 30°C.

[0031] Specifically, in the preparation of the metal solution, the raw materials of the precious metals include at least two of RuCl3, IrCl3, CeCl3 and PtCl2. Users can choose to combine two or more of these precious metals according to actual needs. Among them, the concentration ranges of RuCl3, IrCl3, CeCl3 and PtCl2 after dissolving in pure water are respectively 30-40g / L, 40-60g / L, 35-75g / L and 30-80g / L. This concentration ensures the content of precious metals in the electrolyte, which is beneficial to the subsequent electrolysis reaction.

[0032] The stabilizer is a mixed solution of PUB (polyquaternium-2), BPC (1-benzylpyridine-3-carboxylate) and sodium citrate. The concentrations of PUB, BPC and sodium citrate are in the range of 6-8mL / L, 1-3mL / L and 60-80g / L, respectively. It can be understood that PUB has good water solubility and charge stability, and can be used as a stabilizer in electrolyte solutions to help prevent the aggregation and precipitation of precious metal ions; BPC can form complexes with precious metal ions, thereby increasing their stability in solution; and sodium citrate is a commonly used complexing agent and buffer, which can also form stable complexes with precious metal ions in electrolytes to prevent their precipitation.

[0033] Electrodeposition step 30: Use the substrate as the working electrode, the platinum sheet as the counter electrode, and the saturated calomel electrode as the reference electrode in the electrolyte, deposit the precious metal on the substrate under the preset electrodeposition parameters, and obtain the sample after washing and drying.

[0034] Among them, platinum sheet is often used as the counter electrode in electrochemical deposition due to its good conductivity and chemical stability, while saturated calomel electrode has a stable potential and is often used to provide a potential reference in electrochemical experiments. In this step, the working electrode (substrate), counter electrode and reference electrode are placed in the prepared electrolyte and ensure that they are in full contact with the electrolyte, and then the electrodeposition operation is performed with the preset electrodeposition parameters to obtain a sample with a noble metal formed on the working electrode.

[0035] In the electro-deposition step, the electro-deposition parameters include: the electrolyte temperature is 25-30° C., nitrogen is introduced throughout the electro-deposition process, and the precious metal is deposited on the substrate at a voltage of 1.2-1.4V for 4-10 minutes.

[0036] It is understandable that the temperature of the electrolyte has a significant effect on the diffusion rate of the precious metal ions, the electrochemical reaction rate and the structure of the deposited layer. Within this temperature range, the movement rate of the precious metal ions is moderate, which is conducive to the formation of a uniform and dense deposited layer. During the electrodeposition process, the introduction of nitrogen can remove oxygen from the electrolyte and prevent oxidation of the substrate. The voltage is one of the key parameters in the electrodeposition process, which determines the rate and direction of the electrochemical reaction. Within this voltage range, the precious metal ions can undergo a reduction reaction on the substrate to form the desired deposited layer, and within this time range, the deposition reaches the desired thickness.

[0037] Calcination treatment step 40: placing the sample in a tubular furnace for calcination, and then post-processing to obtain a porous transport layer of a PEM electrolyzer.

[0038] Among them, calcination can promote the reduction and crystallization of precious metal ions. The tubular furnace provides a uniform and controllable heating environment, and nitrogen is usually used as a protective gas to prevent the sample from being oxidized during the calcination process. According to the properties of the sample and the performance requirements of the required material, the calcination temperature is controlled at 250-550°C and the calcination time is 1-3 hours.

[0039] After calcination, post-treatment is required to remove residual impurities. Post-treatment includes adding pure water to the calcined sample and cleaning it in an ultrasonic machine for 10 to 15 minutes. The vibration generated by ultrasound can accelerate the movement of tiny particles in the cleaning solution, thereby more effectively removing impurities on the sample surface. The specific cleaning time can be adjusted according to the nature of the sample and the required degree of cleanliness.

[0040] In summary, the present application aims to prepare a porous transport layer of a PEM electrolyzer, which is prepared by the preparation method of the porous transport layer of a PEM electrolyzer as above. The porous transport layer of the PEM electrolyzer prepared by the technical solution of the present application increases the porosity of the porous transport layer by loading precious metals on titanium felt or porous titanium, reduces the contact resistance between the porous transport layer and the membrane electrode, and improves the activity of the electrolyzer, thereby achieving the purpose of improving the performance of the electrolyzer. And the precious metal is loaded on the surface of the substrate by electrodeposition, and the amount of precious metal used is small, which can further reduce the preparation cost to a certain extent.

[0041] A specific embodiment of preparing a porous transport layer of a PEM electrolyzer is further proposed.

[0042] Example 1

[0043] 1) The porous titanium was cut into a size of 6 cm*6 cm, and the PTL was immersed in a mixed solvent of 2-propanol and acetone in an ultrasonic bath for 15 min, and then rinsed with deionized water to remove organic matter and pollutants on its surface to obtain a substrate.

[0044] 2) Metal RuCl3, IrCl3, CeCl3 and PtCl2 were dissolved in pure water to prepare a metal solution, wherein the concentrations of RuCl3, IrCl3, CeCl3 and PtCl2 in the metal solution were 30 g / L, 40 g / L, 75 g / L and 30 g / L, respectively. A stabilizer was then added to the metal solution and stirred for 15 min to obtain an electrolyte, wherein the stabilizer added included 6 mL / L of PUB (polyquaternium-2), 1 mL / L of BPC (1-benzylpyridine-3-carboxylate) and 60 g / L of sodium citrate.

[0045] 3) The substrate is used as the working electrode, the platinum sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode in the obtained electrolyte for electrodeposition. The electrolyte temperature for the electrodeposition operation is 25°C, nitrogen is introduced throughout the electrodeposition process, and the precious metal is electrodeposited on the substrate at a voltage of 1.3V for 4 minutes, and then rinsed with deionized water in large quantities. After natural drying, the sample is obtained.

[0046] 4) The sample was placed in a tubular furnace and calcined with nitrogen. The calcination temperature was 250°C and the calcination time was 1 hour. The calcined sample was then added with pure water and cleaned in an ultrasonic machine for 10 minutes to remove the substances that are easy to fall off the surface, and the final product, i.e., the porous transport layer (PTL) of the PEM electrolyzer, was obtained.

[0047] The performance of the porous transport layer of the PEM electrolyzer prepared in this embodiment was further tested, and the test process included:

[0048] Based on the porous transport layer (PTL) of the PEM electrolyzer prepared in this embodiment, the end plate, gasket, PTL layer and CCM are assembled on the electrolyzer in order, and the power is provided by a DC power supply for testing. The test temperature of the entire test system is 60°C, and a circulating water system is used with a flow rate of 135ml / min to perform polarization curve tests. In other embodiments of the present application, the test method for the prepared porous transport layer (PTL) of the PEM electrolyzer is consistent, and will not be repeated below.

[0049] The electrolytic cell prepared with the porous transport layer of the PEM electrolytic cell obtained in this example is 2A / cm 2 At the current density, the voltage can reach 1.90 V. This indicates that the PTL prepared by this method shows excellent catalytic activity in the electrolyzer, reduces the amount of precious metals, and provides good stability for the membrane electrode. This method can be applied to PEM electrolyzers.

[0050] Example 2

[0051] 1) The porous titanium was cut into a size of 6 cm*6 cm, and the PTL was immersed in a mixed solvent of 2-propanol and acetone in an ultrasonic bath for 15 min, and then rinsed with deionized water to remove organic matter and pollutants on its surface to obtain a substrate.

[0052] 2) Metal RuCl3, IrCl3 and PtCl2 were dissolved in pure water to prepare a metal solution, wherein the concentrations of RuCl3, IrCl3 and PtCl2 in the metal solution were 40 g / L, 60 g / L and 55 g / L, respectively. A stabilizer was then added to the metal solution and stirred for 15 min to obtain an electrolyte, wherein the stabilizer added included 8 mL / L of PUB (polyquaternium-2), 2 mL / L of BPC (1-benzylpyridine-3-carboxylate) and 80 g / L of sodium citrate.

[0053] 3) The substrate is used as the working electrode, the platinum sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode in the obtained electrolyte for electrodeposition. The electrolyte temperature for the electrodeposition operation is 25°C, nitrogen is introduced throughout the electrodeposition process, and the precious metal is electrodeposited on the substrate at a voltage of 1.4V for 8 minutes, and then rinsed with deionized water in large quantities. After natural drying, the sample is obtained.

[0054] 4) The sample was placed in a tubular furnace and calcined with nitrogen. The calcination temperature was 350°C and the calcination time was 1 hour. The calcined sample was then added with pure water and cleaned in an ultrasonic machine for 12 minutes to remove the substances that were easy to fall off the surface, and the final product, i.e., the porous transport layer of the PEM electrolyzer, was obtained.

[0055] The electrolytic cell prepared with the porous transport layer of the PEM electrolytic cell obtained in this example is 2A / cm 2 At the current density, the voltage can reach 1.850 V. This indicates that the PTL assembly prepared by this method shows excellent catalytic activity in the electrolyzer, and reduces the amount of precious metals to a certain extent, providing good stability for the membrane electrode, and this method can be applied to PEM electrolyzers.

[0056] Example 3

[0057] 1) The porous titanium was cut into a size of 6 cm*6 cm, and the PTL was immersed in a mixed solvent of 2-propanol and acetone in an ultrasonic bath for 15 min, and then rinsed with deionized water to remove organic matter and pollutants on its surface to obtain a substrate.

[0058] 2) Metal RuCl3, IrCl3 and CeCl3 were dissolved in pure water to prepare a metal solution, wherein the concentrations of RuCl3, IrCl3 and CeCl3 in the metal solution were 35 g / L, 50 g / L and 35 g / L, respectively. A stabilizer was then added to the metal solution and stirred for 15 min to obtain an electrolyte, wherein the stabilizer added included 7 mL / L of PUB (polyquaternium-2), 3 mL / L of BPC (1-benzylpyridine-3-carboxylate) and 70 g / L of sodium citrate.

[0059] 3) The substrate is used as the working electrode, the platinum sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode in the obtained electrolyte for electrodeposition. The electrolyte temperature of the electrodeposition operation is 25°C, nitrogen is introduced throughout the electrodeposition process, and the precious metal is electrodeposited on the substrate at a voltage of 1.2V for 4 minutes, and then rinsed with deionized water in large quantities. After natural drying, the sample is obtained.

[0060] 4) The sample was placed in a tubular furnace and calcined by nitrogen gas. The calcination temperature was 300°C and the calcination time was 2 hours. The calcined sample was then added with pure water and cleaned in an ultrasonic machine for 13 minutes to remove the substances that were easy to fall off the surface, and the final product, i.e., the porous transport layer of the PEM electrolyzer, was obtained.

[0061] The electrolytic cell prepared with the porous transport layer of the PEM electrolytic cell obtained in this example is 2A / cm 2 At the current density, the voltage can reach 1.87 V. This indicates that the PTL prepared by this method shows excellent catalytic activity in the electrolyzer and reduces the amount of precious metals to a certain extent. This method can be applied to PEM electrolyzers.

[0062] Example 4

[0063] 1) The porous titanium was cut into a size of 6 cm*6 cm, and the PTL was immersed in a mixed solvent of 2-propanol and acetone in an ultrasonic bath for 15 min, and then rinsed with deionized water to remove organic matter and pollutants on its surface to obtain a substrate.

[0064] 2) Metal CeCl3 and PtCl2 were dissolved in pure water to prepare a metal solution, wherein the concentrations of CeCl3 and PtCl2 in the metal solution were 55 g / L and 80 g / L, respectively. A stabilizer was then added to the metal solution and stirred for 15 min to obtain an electrolyte, wherein the stabilizer added included 7.5 mL / L of PUB (polyquaternium-2), 2 mL / L of BPC (1-benzylpyridine-3-carboxylate) and 70 g / L of sodium citrate.

[0065] 3) The substrate is used as the working electrode, the platinum sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode in the obtained electrolyte for electrodeposition. The electrolyte temperature of the electrodeposition operation is 25°C, nitrogen is introduced throughout the electrodeposition process, and the precious metal is electrodeposited on the substrate at a voltage of 1.2V for 4 minutes, and then rinsed with deionized water in large quantities. After natural drying, the sample is obtained.

[0066] 4) The sample was placed in a tubular furnace and calcined by nitrogen gas. The calcination temperature was 500°C and the calcination time was 2 hours. The calcined sample was then added with pure water and cleaned in an ultrasonic machine for 15 minutes to remove the substances that are easy to fall off the surface, and the final product, i.e., the porous transport layer of the PEM electrolyzer, was obtained.

[0067] The electrolytic cell prepared with the porous transport layer of the PEM electrolytic cell obtained in this example is 2A / cm 2 At the current density, the voltage can reach 1.86 V. This indicates that the PTL prepared by this method shows excellent catalytic activity in the electrolyzer and reduces the amount of precious metals to a certain extent. This method can be applied to PEM electrolyzers.

[0068] Comparative Example

[0069] After the porous titanium was cut into a size of 6 cm*6 cm, it was immersed in an ultrasonic bath in a mixed solvent of 2-propanol and acetone for 15 min, and then rinsed with deionized water to remove organic matter and pollutants on its surface to obtain a PTL sheet.

[0070] In this example, the prepared PTL is assembled on the electrolytic cell in a certain order, including the end plate, gasket, PTL layer and CCM, and the test is carried out by providing power through a DC power supply. The test temperature of the entire test system is 60°C, and a circulating water system is used with a flow rate of 135ml / min to carry out the polarization curve test.

[0071] The electrolytic cell prepared with the PTL sheet obtained in this example is at 2A / cm 2 At the current density, the voltage can reach 2V, and the activity is poor, indicating that the PTL prepared by this method cannot show excellent catalytic activity in the electrolytic cell.

[0072] The above embodiments and comparative examples are only partial selections of the technical solutions of the present application. When conducting experiments, the substrate in the present application can also be prepared based on titanium felt, and the preparation of the porous transport layer of the PEM electrolyzer can be selected based on the same parameter conditions as in Examples 1-4 to obtain Examples 5-8, and a comparative example of preparing the porous transport layer of the PEM electrolyzer with only titanium felt can be set accordingly to compare and analyze the performance differences. Regardless of the preparation method of the substrate, each parameter in each preparation step can be adjusted within the protection scope of the present application.

[0073] The polarization curve test performance of the porous transport layer of the PEM electrolyzer prepared in Examples 1-4 and Comparative Examples of this application is as follows: Figure 2 shown.

[0074] The above description is only a partial or preferred embodiment of the present application. Neither the text nor the drawings can limit the scope of protection of the present application. All equivalent structural changes made using the contents of the present application specification and drawings under the overall concept of the present application, or direct / indirect application in other related technical fields are included in the scope of protection of the present application.

Claims

1. A method for preparing a porous transport layer of a PEM electrolyzer, characterized in that: include: Substrate preparation step: cutting the titanium-based sheet into a preset size and obtaining the substrate after pretreatment; The titanium-based sheet is titanium felt or porous titanium; The electrolyte preparation step is: dissolving the precious metal in pure water to obtain a metal solution, adding a stabilizer to the metal solution, and stirring to obtain an electrolyte; Electrodeposition step: using the substrate as a working electrode, a platinum sheet as a counter electrode, and a saturated calomel electrode as a reference electrode in the electrolyte, depositing the noble metal on the substrate under preset electrodeposition parameters, and obtaining a sample after washing and drying; Calcination treatment step: placing the sample in a tubular furnace for calcination, and then post-processing to obtain a porous transport layer of a PEM electrolyzer.

2. The method for preparing a porous transport layer of a PEM electrolyzer according to claim 1, characterized in that: In the substrate preparation step, the cutting size of the titanium-based sheet is not less than 5*5 cm.

3. The method for preparing a porous transport layer of a PEM electrolyzer according to claim 2, characterized in that: The pretreatment comprises immersing the titanium-based sheet in a mixed cleaning solvent of 2-propanol and acetone in an ultrasonic bath for 15 to 20 minutes, and then rinsing with deionized water.

4. The method for preparing a porous transport layer of a PEM electrolyzer according to claim 1, characterized in that: In the electrolyte preparation step, the precious metal includes at least two of RuCl3, IrCl3, CeCl3 and PtCl2; Among them, the concentration ranges of RuCl3, IrCl3, CeCl3 and PtCl2 after dissolving in pure water are respectively 30-40g / L, 40-60g / L, 35-75g / L and 30-80g / L.

5. The method for preparing a porous transport layer of a PEM electrolyzer according to claim 4, characterized in that: The stabilizer is a mixed solution of PUB, BPC and sodium citrate, wherein the concentrations of the PUB, the BPC and the sodium citrate in the stabilizer are in the ranges of 6-8 mL / L, 1-3 mL / L and 60-80 g / L, respectively.

6. The method for preparing a porous transport layer of a PEN electrolytic cell according to claim 5, characterized in that: The stirring time is 15 to 20 minutes, and the stirring temperature is 25 to 30°C.

7. The method for preparing a porous transport layer of a PEN electrolytic cell according to claim 1, characterized in that: In the electro-deposition step, the electro-deposition parameters include: the electrolyte temperature is 25-30° C., nitrogen is introduced throughout the electro-deposition process, and the noble metal is deposited on the substrate at a voltage of 1.2-1.4V for 4-10 minutes.

8. The method for preparing a porous transport layer of a PEN electrolytic cell according to claim 1, characterized in that: In the calcination step, nitrogen is introduced into the tubular furnace to calcine the sample at a temperature of 250 to 550° C. for 1 to 3 hours.

9. The method for preparing a porous transport layer of a PEN electrolytic cell according to claim 8, characterized in that: The post-treatment includes adding pure water to the calcined sample and then washing it in an ultrasonic machine for 10 to 15 minutes.

10. A porous transport layer of a PEM electrolyzer, characterized in that: The porous transport layer of a PEM electrolyzer is prepared by the method for preparing the porous transport layer of a PEM electrolyzer as described in any one of claims 1 to 9.